The analysis of coordinated effects in EU merger control: where do we stand after Sony/BMG and Impala? - Gisela Aigner; Oliver Budzinski; Arndt Christiansen (Universität Duisburg-Essen, Fachbereich Wirtschaftswissenschaften, 2007)
The recent Impala Judgment by the CFI on the Sony/BMG Decision by the Commission represents the most important ruling on collective dominance since Airtours. We review both the Decision and the Judgment and derive implications for the institutional and substantive development of EU Merger Control. Firstly, Impala introduces an ambitious symmetric standard of proof for prohibition and clearance decisions by the Commission. While alleviating fears of an increasing number of false positives in the aftermath of Airtours, this entails the problem of how to deal with cases in which neither the existence, nor the absence of anticompetitive effects can be proven to the required standard. Secondly, the ongoing process of increasing the role of third parties in European Merger Control is fuelled. Thirdly, Impala has the potential to herald a comeback of coordinated effects analysis, further precising the conditions for establishing this kind of anticompetitive effect. Additionally, given the characteristics of the music industry, we criticise a lack of in-depth economic analysis of non-price competition issues, such as innovations and product diversity.
Keywords: K21; L41; L13; L82; 330; merger control; coordinated effects; standard of proof; music industry; collusion; Impala; Sony/BMG; Fusionskontrolle; Musikwirtschaft; Wettbewerbsbeschränkung; EU-Staaten